A bibliometric analysis of challenges and advancements in the integrated application of nanoparticles and chimeric antigen receptor T cell therapy - Yang Gao; Yang Zhou; Xiaolin He; Hongwei Lin; Keying Fang; Qijun Hou; Huafang Wang; Honghao Zhang; Yixi Zhang; Yuhua Li (Human Vaccines & Immunotherapeutics)
In recent years, the integration of nanoparticles with chimeric antigen receptor T-cell (CAR-T) therapy has advanced rapidly, garnering considerable attention from both academic and industrial sectors. However, a comprehensive analysis of key trends and emerging frontiers in this interdisciplinary field remains lacking. To address this gap, we conducted a bibliometric analysis of 515 publications indexed in the Web of Science Core Collection from 2013 to 2024. Using VOSviewer, CiteSpace, and R-bibliometrix, we analyzed publication trends, influential journals, national and institutional contributions, leading authors, and high-impact references. Keyword co-occurrence analyses were performed in VOSviewer, applying a minimum occurrence threshold of five. Citation bursts and clustering analyses of references and keywords were conducted using CiteSpace with default detection settings. Our analysis revealed major research hotspots, especially the optimization of CAR-T cell manufacturing processes and strategies to overcome barriers within the immunosuppressive tumor microenvironment. Looking forward, research is expected to focus increasingly on nanotechnologies such as lipid nanoparticles, precision cell tracking, and siRNA delivery platforms. These innovations hold substantial promise for enhancing the therapeutic efficacy of CAR-T therapies, particularly in the treatment of solid tumors, where conventional approaches remain inadequate. By identifying emerging directions and influential research trends, our analysis highlights the dynamic synergy between nanoparticles and CAR-T therapies, helping to fuel groundbreaking advances in tumor immunotherapy. This study provides data-driven insights that inform clinical trial design, foster interdisciplinary collaboration, and demonstrate the field’s strong potential to transform future cancer treatment paradigms.